Dynamics of Morocco’s outward FDI in Sub Saharan Africa countries - SALMA RCHILY (Moroccan Journal of Quantitative and Qualitative Research)
Investments are likely to enhance economic growth; and, in many ways, they strengthen local savings and local investment while being a source of job creation. The Moroccan government views foreign investment as an important vehicle for development. In recent years, morocco has gained the upper hand in its conflict in western Sahara and has been increasing its politically and economically footprints on the African continent, a district of interest, since independence.